Democratic leadership of an organization and its effect on work motivation of millennial employees: A case study on the Information Technology sector in Vietnam - Dang, Mai Tuyet (2018)
The purpose of this research is to evaluate the effect of Democratic leadership on the work motivation of millennial employees working in the Information Technology (IT) industry in Vietnam. The study uses primary data collected from a survey with the employees who are called millennials, being born between 1982 and 2004 (Horovitz, 2012). A relationship between Democratic leadership and work motivation of millennial employees working in the IT industry in Vietnam is examined by conducting multiple linear regression analysis using SPSS as the analytical method to test hypotheses in this study. The methodology to answer the research questions developed consists of a quantitative study of the evaluations of millennial employees in the IT sector in Vietnam towards Democratic leadership style. This study contributes to the leadership practice of IT companies in Vietnam applied to the millennial generation which is progressively emerging into their organizations nowadays.